Pengaruh Media Pendidikan Kesehatan terhadap Pengetahuan dan Sikap Remaja Perempuan Terhadap Vaksin Human Papilloma Virus (HPV) - Jum Natosba; Almuslimiati Ramadhani; Khoirul Latifin; Ulfa Nur Rohmah (PT.Mantaya Idea Batara, 2026)
Background: Insufficient knowledge of reproductive health among female adolescents contributes to inadequate prevention and early detection of cervical cancer. Cervical cancer frequently develops in early adulthood, despite being preventable through the timely administration of the Human Papillomavirus (HPV) vaccine. This study evaluates the effectiveness of health education media in improving female adolescents' knowledge and attitudes toward the HPV vaccine. Methods: A quasi-experimental quantitative design with a pretest- posttest control group was employed. The sample consisted of 66 participants selected via probability sampling with stratified sampling. Result: Statistical analysis indicated that both the engklek and crossword puzzle intervention groups demonstrated significant improvements in knowledge and attitudes following the intervention (p < 0.05), while the control group showed no significant changes (p < 0.05). One-way ANOVA revealed significant differences in knowledge and attitudes among the engklek, crossword, and control groups (p = 0.000). Post hoc and N-gain analyses indicated that crossword puzzles were the most effective in enhancing adolescents’ knowledge. Conclusion: Crossword puzzle media can serve as an effective tool for disseminating information about the HPV vaccine. Enhanced dissemination is anticipated to increase HPV vaccine coverage and reduce cervical cancer risk.